Pengaruh Problem-Based Learning Terhadap Peningkatan Kemampuan Berpikir Kritis Siswa Pada Materi Statistika - Amalin Aisyah Siregar; Laili Habibah Pasaribu; Lily Rohanita (JNPM (Jurnal Nasional Pendidikan Matematika), 2026)
Statistics learning still largely uses conventional approaches that are not optimal in developing students' critical thinking skills. This study aims to examine the effect of the implementation of the Problem-Based Learning (PBL) model on improving students' critical thinking skills in statistics material. This study used a quantitative approach with a quasi-experimental design. Data collection was carried out through critical thinking ability tests given before and after the implementation of PBL in the experimental group, then analyzed using the Wilcoxon Signed Ranks test. The results showed a significant increase in students' critical thinking skills after the implementation of the PBL model. The statistical analysis produced a Z value = −4.545 with an asymptotic significance value (2-tailed) of 0.000 (α < 0.05), which indicates a significant difference between the pretest and posttest scores. These findings indicate that the PBL model has a significant effect on improving students' critical thinking skills in statistics learning. The results of this study are expected to provide theoretical contributions in the development of Problem-Based Learning as well as practical implications for teachers in efforts to improve the quality of statistics learning.